2017
DOI: 10.5301/ejo.5001009
|View full text |Cite
|
Sign up to set email alerts
|

Microbial characteristics of post-traumatic infective keratitis

Abstract: A shift of practice in post-traumatic infective keratitis should be considered in tropical countries to include Gram-negative cover. Work safety practices with vigilance in initiating treatment and education by front-line physicians such as ophthalmology and general practitioners should be reinforced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 14 publications
2
16
1
2
Order By: Relevance
“…For our patient, corneal scraping and culture were performed because of the emergence of a corneal ulcer at an early stage of the disease; the results confirmed bacterial infection. Multiple authors have shown that bacteria causing mixed keratitis are generally sensitive to the fluoroquinolone class of antibiotics, 5,7,20,21 which was also confirmed in this case. Our first choice was gatifloxacin because-in addition to the above factors-its ability to permeate into the eyes is much greater than that of the commonly used levofloxacin; moreover, its half-life is longer than that of moxifloxacin.…”
Section: Clinical Practice Pointssupporting
confidence: 83%
See 2 more Smart Citations
“…For our patient, corneal scraping and culture were performed because of the emergence of a corneal ulcer at an early stage of the disease; the results confirmed bacterial infection. Multiple authors have shown that bacteria causing mixed keratitis are generally sensitive to the fluoroquinolone class of antibiotics, 5,7,20,21 which was also confirmed in this case. Our first choice was gatifloxacin because-in addition to the above factors-its ability to permeate into the eyes is much greater than that of the commonly used levofloxacin; moreover, its half-life is longer than that of moxifloxacin.…”
Section: Clinical Practice Pointssupporting
confidence: 83%
“…The treatment of double microbial infection-derived keratitis has been widely reported, [4][5][6] with infection mostly caused by two fungal species, a mixture of fungal and bacterial pathogens, or a mixture of a fungus and Acanthamoeba; in contrast, keratitis caused by triple infection has been extremely rare, constituting only 1.16% of all reported cases of corneal infection. 7 The largest retrospective study of such infections thus far was conducted by Ray et al, 7 who reported that the isolated microorganisms consisted of only two species (bacterial and/or fungal), including two bacterial species (e.g., Neisseria meningitidis and Pseudomonas aeruginosa).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corneal cells of the human eye form a non-polar apical barrier, which is important for function and protection against infection [41]. Infections usually arise after physical damage to the cornea by opportunistic pathogens [41,42]. We found that fully confluent HCE-T cells were not susceptible to infection by PA103 ( Figure 4A) Figure 4C).…”
Section: A Scratch and Infection Assay To Evaluate The Therapeutic Pomentioning
confidence: 87%
“…However, these were performed on all types of microbial keratitis regardless of etiology [22]. In the study of Lim et al [23], no Gram-positive organisms were isolated in culture-positive eyes. Pseudomonas aeruginosa was the commonest Gram-negative organism isolated in their study.…”
Section: Discussionmentioning
confidence: 99%